Bispecific antibody-targeted T-cell therapy for acute myeloid leukemia - Kubicka, Ewa; Lum, Lawrence G.; Huang, Manley; Thakur, Archana (Frontiers in Immunology, 2022)
The management of relapsed or refractory acute myeloid leukemia (AML) continues to be therapeutically challenging. Non-toxic immunotherapy approaches are needed to provide long-term anti-leukemic effects. The goal of this study was to determine whether activated T cells (ATCs) armed with bispecific antibodies (BiAbs) could target and lyse leukemic and leukemic stem cells (LSCs). Anti-CD3 × anti-CD123 BiAb (CD123Bi) and anti-CD3 × anti-CD33GO (gemtuzumab ozogamicin [GO]) BiAb (CD33GOBi) were used to arm ATCs to produce bispecific antibody armed activated T cells (designated CD123 BATs or CD33GO BATs) to target AML cell lines, peripheral blood mononuclear cells from AML patients, and in vivo treatment of AML in xenogeneic NSG mice engrafted with leukemic cells. BATs exhibited high levels of specific cytotoxicity directed at AML cell lines at low 1:1 or 1:2 effector-to-target (E:T) ratios and secrete Th1 cytokines upon target engagement. In vivo study in AML-engrafted NSG mice showed significantly prolonged survival in mice treated with CD33GO BATs (p < 0.0001) or CD123 BATs (p < 0.0089) compared to ATC-treated control mice. Patient samples containing leukemic blasts and LSCs when treated with CD33GO BATs or CD123 BATs for 18 h showed a significant reduction (50%–100%; p < 0.005) in blasts and 75%–100% reduction in LSCs (p < 0.005) in most cases compared to unarmed ATCs. This approach may provide a potent and non-toxic strategy to target AML blasts and LSCs and enhance chemo-responsiveness in older patients who are likely to develop recurrent diseases.